Global Financial Crisis: A Critique on the Book Freefall; America, Free Markets and the Sinking of the World Economy - Seyed Hossein Mirjalili (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
In this paper, the book entitled “Freefall; America, Free Markets and the Sinking of the World Economy” is reviewed which is about the causes of the financial crisis of 2007-2009 in the US economy. The author is a world-renowned economist and the book has been translated into more than 20 languages. In this review, for collecting information, the books and articles are used as scientific documents, and for analyzing information, the descriptive-comparative method was applied. The book has a logical consistency. It begins with the origins of the crisis, and then discusses the consequences, policies, motivations, and necessary reforms in the economy and the attitude of American society. The shortcomings of the translated book, in addition to typographical errors and the need to revise some jargons, are the lack of translation of the footnotes of the chapters, which make up 73 pages of the translated book. Despite the relative coherence of the work, the translated book suffers from the exclusion of America from the title of the book, despite the fact that the whole book is about the American economy. The hopeful statements appeared at end of the book without providing a solution, and lack of analysis for the effects of Reagan economics as a background of the financial crisis, and also the neglect of systemic risk. The book highlights the adverse effects of materialism, extremist individualism, and market fundamentalism on American society. It also explains the neoclassical foundations of policies that led to the financial crisis and the battle of ideas in economics.